Implementasi Model Problem Based Learning Dalam Meningkatkan Hasil Belajar Matematika Siswa Sekolah Dasar - Fauzi, Rifqi Ahmad; Manan, Nanan Abdul; Fitriyani, Yani (Fakultas Agama Islam Universitas Ibn Khaldun Bogor, 2023)
This study aims to determine the effect of the Problem Based Learning learning model on improving mathematics learning outcomes at the Guidance Beach Studio in Kuala Lumpur, Malaysia. The method used in this study used the pre-experimental method by giving treatment or treatment to the research sample. The number of samples in this study were all students of the Kuala Lumpur Inner Beach Guidance Studio, Malaysia, totaling 6 people using the one group pretest and posttest design. The results of this study can be seen from the results of calculations with the t test, namely the two different average test, where the mean or average value in the pretest before the treatment is given is 51.666 while the mean or average value in the posttest results after the treatment is given is 81.666 with a level significance of 0.00 <0.05, which means that the value after the treatment is given is greater than the value before the treatment or treatment is given with a significance value of less than 0.05. This means that there is a significant difference between before and after being given treatment or treatment using the Problem Based Learning learning model. Therefore, the Problem Based Learning learning model has an effect on improving students' mathematics learning outcomes at the Kuala Lumpur Inner Beach Guidance Studio, Malaysia. The results of this research are expected to be useful for related parties who can use them, such as Guidance Center managers, teachers, students, and further researchers.